State Development Plans-Review of Progress - Planning Commission (Planning Commission, 1958)
The actual expenditure incurred during 1956-57 came to Rs. 24 95 crores. the revised estimate for 1957-58 stands at Rs. 34.60 crores. the agreed outlay for 1958-59 is Rs. 30.02 crores. Even if it is assumed that there would be no shortfalls in the second and third years of the Plan period, the total expenditure for the first three years will not exceed Rs. 89.57 crores which gives a percentage of 51 with reference to the total outlay. The balance of outlay for the last two years comes to about Rs. 85 crores. It is doubtful if resources to that extent would be forthcoming.
Government of India Planning Commission